Simplify: (1 + i)(1 - i)

Answer
a. -2i
b. 2
c. 2i
d.-2

2 answers

(1)(1 - i) + (i)(1 - i)
now simplify.
note: i^2=-1
1 - i + i -i^2 = 1 - (-1) = ?
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify the expression.(-4)^-6(-4)^-7 My answer: -4 Simplify and give the answer in scientific notation. (5 X 10^6((3 X 10^5)
    1. answers icon 6 answers
    1. answers icon 1 answer
  3. Simplify the complex fraction:x+(4x/y)/(7/3x) I know that the answer is 3x^2(y+4)/7y. I don't know how to get this answer. Can
    1. answers icon 3 answers
more similar questions